L'orientation professionelle fe filles et des femmes: directives d'exercice de la profession - Ward, Valerie; Bezanson, Lynne (Canadian Journal of Counselling and Psychotherapy, 2011)
Guidelines for the Career Counselling of Girls and Women were drafted by a Collaborative Action Committee of which the authors were members. The Guidelines were an important component of a framework for action for labour market equality and were subsequently endorsed by the provincial Ministers Responsible for the Status of Women and Ministers with Labour Market Responsibilities. They are presented as blueprints for the consideration and action of the counselling profession at all levels, from practitioners to policy makers.